Modifications in room temperature ferromagnetism by dense electronic excitations in Zn0.9Mg0.1O thin films - Kumar, Parmod; Malik, Hitendra K.; Gautam, S.; Chae, K. H.; Asokan, K.; Kanjilal, D. (ELSEVIER SCIENCE SA, 2017)
Present study shows that dense electronic excitations caused by ion beam irradiation in Zn0.9Mg0.1O films lead to significant changes in room temperature ferromagnetism. It is found that defects are playing dominant role in the modification of various physical properties including ferromagnetic behaviour. Presence of defects were investigated through photoluminescence spectroscopy along with local electronic structure study using X-ray absorption spectroscopy. This novel observation is relevant to get further insight into ferromagnetic origin and maybe applied to tune magnetic properties for spintronic applications. A strong correlation exists between the ferromagnetic properties and defects produced during high energy irradiation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ZNO; MAGNETIZATION